Evaluation of the Haemophilus influenzae EUCAST and CLSI disc diffusion methods to recognize aminopenicillin and amoxicillin/clavulanate resistance. (25th June 2020) - Fernando, S A; Pang, S; McKew, G L; Phan, T; Merlino, J; Coombs, G W; Gottlieb, T
Abstract: Objectives: Implementation of EUCAST susceptibility testing in an Australian hospital laboratory demonstrated higher rates of aminopenicillin and amoxicillin/clavulanate resistance in Haemophilus influenzae than previously recognized. This study aimed to better define the variability in the detection of β-lactam resistance based on EUCAST and CLSI disc diffusion (DD) methodology, by comparison with the recommended reference method, broth microdilution (BMD), and by concordance with genomic analysis. Methods: A total of 100 random H. influenzae isolates were assessed for ampicillin and amoxicillin/clavulanate susceptibility by EUCAST and CLSI DD and BMD. WGS was used to analyse the ftsI gene of a subset of isolates with β-lactam resistance, other than that due to isolated β-lactamase production. Results: Of the 100 isolates, 32 were categorized as either β-lactamase negative, ampicillin resistant (BLNAR) ( n =  18) or β-lactamase positive, amoxicillin/clavulanate resistant (BLPACR) ( n =  14) by EUCAST DD. All 18 EUCAST BLNAR isolates were genotypically confirmed by WGS. Five of 18 BLNAR isolates were concordant by CLSI DD, 12 by EUCAST BMD and 4 by CLSI BMD. Nine of 14 EUCAST BLPACR isolates were confirmed by WGS; the remaining 5 were 1 mm below the EUCAST DD breakpoint. Only one isolate was detected as BLPACR by CLSI DD. Group III mutations associated with high-level ampicillin resistance were identified in 10/32 isolates. Conclusions: The EUCAST DD susceptibility method is more reliable than either CLSI or BMD for the detection of genotypically defined BLNAR resistance. However, accurate categorization of amoxicillin/clavulanate resistance remains problematic. Continuous and reproducible surveillance of resistance is needed; for this to be possible, robust susceptibility methods are required.